The Influence of Receivables Turnover and Inventory Turnover on Profitability at PT Indofood Sukses Makmur Tbk (Case Study of the Indonesia Stock Exchange 2016-2023) - Yulia Saputri; Pitri, Tedi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine whether inventory and receivables turnover affect the profitability of PT Indofood Sukses Makmur Tbk simultaneously or gradually. The subject of this investigation is a manufacturing company listed on the Indonesia Stock Exchange. In this study using a descriptive method with a quantitative approach. The data used are secondary data and statistical methods using the SPSS26 program. The determination coefficient test shows that the variables of receivables turnover and inventory turnover affect profitability by 89.0% and the partial hypothesis test of the receivables turnover value -1.699 <1.699 has a significant negative effect on profitability, and the inventory turnover value is 13.917> 3.328 has a significant positive effect on profitability and the simultaneous hypothesis test with a value of 113.607> 3.328 Therefore, the factors of receivables turnover and inventory simultaneously affect profitability